Butterfly Diversity in Sal Forests of Kharsawan Region of Seraikela-Kharsawan District, Kolhan Division, Jharkhand, India - Reddy, B.Thirupam; Rajgopal, N.N.; Shashank, P. R.; M. Baig, Mohammed; Srinivas, C.; Ashoka, K.S.; Anaray Ana, K.Sathya (Indian Forester, 2023)
Jharkhand is home for diverse fauna and flora and the present study of butterflies through visual encounters over a 2-year period in the Kharsawan region of Seraikela-Kharsawan district recorded 84 species of butterflies belonging to 61 genera representing 6 families (Hesperiidae, Lycaenidae, Nymphalidae, Papilionidae, Pieridae and Riodinidae). Among 84 species 11 species of three different families are first records for the state of Jharkhand and 15 species of five families are protected under Indian Wildlife (Protection) Act, 1972(WPA).